Досвід міжнародних організацій в процесі регулювання розвитку людського потенціалу - Яковенко, Р. В.; Yakovenko, R. (Кропивницький : сайт www.surma-ua, 2018)
У статті створено теоретико-економічні передумови для формування ефективного механізму впливу на демографічні процеси та формування інтелектуально повноцінного людського потенціалу в сучасних умовах на рівні міжнародної економічної співпраці. This article is intended for disclosure the trends of modern international market and Ukraine participation in it. We study the experience of international organizations toward advanced human reproduction and determined its role in Ukraine.
The experience of international organizations in the process of regulating the development of human potential
Keywords: людський потенціал; інформаційні потреби; якість життя; міжнародна співпраця; human potential; information needs; quality of life; international cooperation